2022
DOI: 10.21203/rs.3.rs-1508125/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of anterior debridement and bone grafting with fusion using internal fixation combined with anti-tuberculosis chemotherapy in the treatment of subaxial cervical tuberculosis

Abstract: Background: To evaluate the efficacy of anterior debridement and bone grafting with fusion using internal fixation (BFIF) combined with anti-tuberculosis chemotherapy in the treatment of subaxial cervical spine tuberculosis (SCS-TB).Methods: Clinical and radiographic data of patients with SCS-TB treated by anterior debridement and BFIF at our hospital from January 2010 to December 2017 were analyzed retrospectively. The SCS sagittal parameters at the preoperative, postoperative, and final follow-up were docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Surgical treatment for spinal TB was proven to be effective, 12–14 and some studies have shown that surgical treatment was a favorable factor for the prognosis of patients with spinal TB. 15 , 16 And some studies advocated aggressive surgery for spinal TB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical treatment for spinal TB was proven to be effective, 12–14 and some studies have shown that surgical treatment was a favorable factor for the prognosis of patients with spinal TB. 15 , 16 And some studies advocated aggressive surgery for spinal TB.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Consequently, extensive attention has been given to shortening anti-TB chemotherapy to eliminate adverse consequences during tuberculosis management. 11 Surgical treatment for spinal TB was proven to be effective, [12][13][14] and some studies have shown that surgical treatment was a favorable factor for the prognosis of patients with spinal TB. 15,16 And some studies advocated aggressive surgery for spinal TB.…”
Section: Introductionmentioning
confidence: 99%